Knowledge co-production for identifying indicators and prioritising solutions for food and land system sustainability in Australia - Romy L. Zyngier; Carla L. Archibald; Brett A. Bryan; Haley Lambert; Enayat A. Moallemi; Mark Elliott; Mark Lawrence; Jane Hutchinson; Lauren T. Bennett; Timothy Reeves; Matthew Pryor; Ulrika Lindholm; et al. (Sustainability Science, 2024)
Achieving sustainable Australian food and land systems requires the rapid implementation and scaling up of a broad suite of solutions to meet the Sustainable Development Goals (SDGs). Decision-making frameworks are needed to identify suitable indicators and prioritise solutions at national scales to inform sustainability transitions. Using a knowledge co-production framework, we convened 150 stakeholders from 100 + organisations to identify 18 nationally relevant indicators that aligned with critical SDGs describing a sustainable food and land system for Australia, in addition to 78 key solutions (supply- and demand-side) to enable progress against these indicators. We then asked subject matter experts to code the impact of each solution on each indicator using an adapted interaction mapping method accounting for uncertainty. The solution category ‘Protecting and restoring nature’, which included solutions targeting conservation and restoration, showed the highest potential for capturing synergies and avoiding trade-offs across multiple indicators. This category exhibited 34.6% of total major synergies, supporting the achievement of clean water and sanitation (SDG6), economic growth (SDG12), life under water (SDG14), and life on land (SDG15). The solution category ‘Carbon sequestration’, which included technological and biological carbon dioxide removal solutions, had the highest number of trade-offs with individual sustainability indicators (42.3%), particularly those relating to zero hunger (SDG2), wellbeing (SDG3), SDG6, SDG14, and SDG15. Our framework can be used to inform future research investment, support the prioritisation of solutions for quantitative modelling, and inform discussions with stakeholders and policymakers for transforming national-scale food and land systems in alignment with the SDGs.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

New Oldowan locality Sare-Abururu (ca. 1.7 Ma) provides evidence of diverse hominin behaviors on the Homa Peninsula, Kenya - Emma M. Finestone; Thomas W. Plummer; Thomas H. Vincent; Scott A. Blumenthal; Peter W. Ditchfield; Laura C. Bishop; James S. Oliver; Andy I.R. Herries; Christopher Vere Palfery; Timothy P. Lane; Elizabeth McGuire; Jonathan S. Reeves; et al. (Journal of Human Evolution, 2024)

Understanding vessel noise across a network of marine protected areas - Megan F McKenna; Timothy J Rowell; Tetyana Margolina; Simone Baumann-Pickering; Alba Solsona-Berga; Jeffrey D Adams; John Joseph; Ella B Kim; Annebelle CM Kok; Anke Kügler; Marc O Lammers; Karlina Merkens; et al. (Environmental Monitoring and Assessment, 2024)
Protected areas are typically managed as a network of sites exposed to varying anthropogenic conditions. Managing these networks benefits from monitoring of conditions across sites to help prioritize coordinated efforts. Monitoring marine vessel activity and related underwater radiated noise impacts across a network of protected areas, like the U.S. National Marine Sanctuary system, helps managers ensure the quality of habitats used by a wide range of marine species. Here, we use underwater acoustic detections of vessels to quantify different characteristics of vessel noise at 25 locations within eight marine sanctuaries including the Hawaiian Archipelago and the U.S. east and west coasts. Vessel noise metrics, including temporal presence and sound levels, were paired with Automatic Identification System (AIS) vessel tracking data to derive a suite of robust vessel noise indicators for use across the network of marine protected areas. Network-wide comparisons revealed a spectrum of vessel noise conditions that closely matched AIS vessel traffic composition. Shifts in vessel noise were correlated with the decrease in vessel activity early in the COVID-19 pandemic, and vessel speed reduction management initiatives. Improving our understanding of vessel noise conditions in these protected areas can help direct opportunities for reducing vessel noise, such as establishing and maintaining noise-free periods, enhancing port efficiency, engaging with regional and international vessel quieting initiatives, and leveraging co-benefits of management actions for reducing ocean noise.

Historic palaeobotanical collection reveals in situ microspores and pollen from Early Carboniferous (Tournaisian) ovules from the Ballagan Formation of Scotland - Emma Reeves; John E.A. Marshall; Carys Bennett; Sarah Davies; Timothy Kearsey; David Millward (Review of Palaeobotany and Palynology, 2023)

Predicting phenotypes from genetic, environment, management, and historical data using CNNs - Jacob D. Washburn; Emre Cimen; Guillaume Ramstein; Timothy Reeves; Patrick O’Briant; Greg McLean; Mark Cooper; Graeme Hammer; Edward S. Buckler (Theoretical and Applied Genetics, 2021)

Advancing the Interpretation of Shallow Water Marine Soundscapes - Megan F. McKenna; Simone Baumann-Pickering; Annebelle C. M. Kok; William K. Oestreich; Jeffrey D. Adams; Jack Barkowski; Kurt M. Fristrup; Jeremy A. Goldbogen; John Joseph; Ella B. Kim; Anke Kügler; Marc O. Lammers; et al. (Frontiers in Marine Science, 2021)
Soundscapes offer rich descriptions of composite acoustic environments. Characterizing marine soundscapes simply through sound levels results in incomplete descriptions, limits the understanding of unique features, and impedes meaningful comparisons. Sources that contribute to sound level metrics shift in time and space with changes in biological patterns, physical forces, and human activity. The presence of a constant or chronic source is often interwoven with episodic sounds. Further, the presence and intensity of sources can influence other sources, calling for a more integrated approach to characterizing soundscapes. Here, we illustrate this complexity using data from a national-scale effort, the Sanctuary Soundscape Monitoring Project (SanctSound), an initiative designed to support collection of biological, environmental, and human use data to compliment the interpretation of sound level measurements. Using nine examples from this diverse dataset we demonstrate the benefit of integrating source identification and site features to interpret sound levels across a diversity of shallow water marine soundscapes (<150 m). Sound levels from sites in high human use areas reflect the anthropogenic influences on the soundscape, especially when measuring broad frequency bands, whereas sites with relatively low human activity and high sound levels reveal biological features of the soundscape. At sites with large tidal changes, sound levels correlated with the magnitude of tidal flow, and sound levels during high tidal flow periods were similar to sound levels at sites near commercial shipping lanes. At sites in relatively close proximity (<30 km), sound levels diverge because of the presence of different proximate sound contributors and propagation features of the site. A review of emerging methodologies for integrated soundscape analysis, including acoustic scenes, provides a framework for interpreting soundscapes across a variety of conditions. With a global growth in monitoring efforts collecting standardized measurements over widely distributed arrays, more integrated methods are needed to advance the utility of soundscapes in marine resource management.

The Roles of the Olivocerebellar Pathway in Motor Learning and Motor Control. A Consensus Paper - Eric J. Lang; Richard Apps; Fredrik Bengtsson; Nadia L Cerminara; Chris I De Zeeuw; Timothy J. Ebner; Detlef H. Heck; Dieter Jaeger; Henrik Jörntell; Mitsuo Kawato; Thomas S. Otis; Ozgecan Ozyildirim; et al. (The Cerebellum, 2017)

A Marine Plant (Spartina Anglica) Invades Widely Varying Habitats: Potential Mechanisms of Invasion and Control - Sally D. Hacker; David Heimer; C. Eric Hellquist; Tabitha G. Reeder; Blain Reeves; Timothy J. Riordan; Megan N. Dethier (Biological Invasions, 2001)

Endogenous estrogen and postmenopausal breast cancer: a quantitative review - Hollie V. Thomas; Gillian K. Reeves; Timothy J.A. Key (Cancer Causes & Control, 1997)